FDI and trade for foreign market entry: theory and evidence from Estonia - Per Botolf Maurseth; Jaan Masso; Rasmus Bøgh Holmen (Baltic Journal of Economics)
This article investigates firms' strategies for international expansion, foreign direct investment (FDI) and exports. We use the framework of Helpman et al. (2004) to illustrate how firm-level productivity differences influence these strategies. We extend this model with multifactor production processes, encompassing both trade in goods and services. The model predicts that trade and FDI can be both substitutes and complements. Our empirical analysis uses detailed Estonian firm-market-level data to explore the model's predictions by estimating the intensive and extensive trade margins and internationalization choices of firms between trade and FDI. The empirical findings indicate that selection into exporting is determined by past productivity. There is evidence consistent with spillover effects in goods exports from other exporters to the same destination. Outward FDI complements both goods and services exports. Our findings underscore the complexity of firms' choices for international expansion, urging a nuanced dichotomy between FDI and exports.